Assessment of Various Complains after Non-Surgical Treatment of Condylar Fracture - Haroon, Asif Nazir Ch., Fahad Khaliq, Husna Shams, Wajeeha Chauhdry, Waqar Hussan Kulachi (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess various complains of patients after non-surgical treatment of condylar fracture. Methodology: A cross-sectional study was performed from October 2021 to October 2022 at the Department of Oral and Maxillofacial Surgery, Nishtar Institute of Dentistry, Multan. The sample size collected was 34 patients using a consecutive non-probability sampling. Using pertinent clinical examination, the patient was assessed for disturbed occlusion, limited mouth opening, deviation of the mouth, pain, and clicking sound. The mean follow-up period was six months. Results: The male-to-female ratio was 1.8: 1, with male predominance. The leading cause of fracture was attributed to incidents involving road traffic accidents (RTAs) (n—26, 76.5%).Twenty-three patients had a positive post-opt complaint after treatment, from which the most complaints presented were with unilateral condylar fracture n=15. The most common complaint presented was TMJ Pain with limited mouth opening n=8(23.5%). Conclusion: Conservative care for unilateral mandibular condyle fractures is a safe treatment approach. However, it can cause a few post-treatment functional complaints, the most frequent of which is TMJ pain. To further evaluate the improvement in function and discomfort, more research and consistent long-term follow-ups are required. Keyword: Temporomandibular joint movement (TMJ), TMJ Pain, Maxillomandibular Fixation (MMF)